Structural-semantic and ethno-cultural characteristics of Karachay-Balkar simple verbal paremic statements about dancing - Mussa B. Ketenchiev; Alim K. Appoev (Кавказология, 2023)
This article is devoted to the study of Karachay-Balkarian simple verbal paremic statements about dances in terms of their formal semantic structure and ethno-cultural significance. The paper emphasizes that syntactic constructions structure an incomplete paradigm according to the purpose of the utterance, which includes narrative and motivational expressions. The affirmation/negation paradigm is no less significant. The formal semantic structure of these statements is primarily determined by the lexical meanings and grammatical features of words that occupy the positions of the predicate or predicate. These lexemes include verbs of movement, action, knowledge, skills, vision, etc., which in the sentence structure open positions for subjects, objects and circumstantial specifiers of the corresponding semantics. They reveal significant concepts for archaic choreography contributing to the understanding of ethnic cultural specifics of the Karachai and Balkars. The proverbial and archetypal fund of the people presents several cognitive characteristics inherent in national dances, as well as dancers participating in various kinds of solemn and other events, determined by the mentality of the ethnic group.